Selective serotonin reuptake inhibitor use in hip fracture patients: a Danish nationwide prevalence study - Bruun, Stine B; Petersen, Irene; Kristensen, Nickolaj R; Cronin-Fenton, Deirdre; Pedersen, Alma B (Acta Orthopaedica, 2018)
Background and purpose — Selective serotonin reuptake inhibitors (SSRIs) are often used in the elderly and are associated with adverse effects. Therefore, it is important to ascertain the prevalence of SSRI use in fragile and surgerytreated hip fracture patients. Methods — This population-based prevalence study included Danish hip fracture patients aged ≥ 65 years operated in 2006–2016 (n = 68,607) and matched individuals from the background population (n = 343,020). Using Poisson regression, prevalence risk ratios (PRRs) with 95% confidence intervals (CIs) were estimated to compare hip fracture patients with the general population, and to estimate the association between hip fracture patient characteristics and SSRI prescriptions. Results — The prevalence of SSRI use among hip fracture patients was 23% compared with 12% in the general population. During 2006–2016, the prevalence decreased from 26% to 18% among hip fracture patients and from 13% to 10% in the general population. Factors associated with SSRI use in hip fracture patients were age 75–84 years (PRR 1.18, CI 1.13–1.23), age ≥ 85 years (PRR 1.17, CI 1.11–1.22), female sex (PRR 1.13, CI 1.09–1.17), unmarried status (PRR 1.15, CI 1.11–1.19), living in a residential institution (PRR 2.30, CI 2.19–2.40), Charlson comorbidity index (CCI) score 1–2 (PRR 1.50, CI 1.45–1.55), CCI score 3+ (PRR 1.62, CI 1.55–1.69), and several medications. Interpretation — The prevalence of SSRI use was high among hip fracture patients compared with the general population. Our data stress the importance of continued clinical awareness of frailty, comorbidity, and polypharmacy of hip fracture patients and the potentially adverse drug effects of SSRI treatment.